التحري عن Cryptosporidium parvum و Toxoplasma gondii في بعض منتجات اللحوم والحليب (University of Mosul-college of Basic Education, 2011)
أجريت هذه الدراسة على عدد 45 عينة من منتجات اللحوم متمثلة في لحوم مفرومة وسجق مستورد ولنشون بواقع 15 عينة من كل نوع و 60 عينة من حليب الأبقار الطري والأغنام وتم فحص تلك العينات عن مدى تلوثها بالطفيليات الأولية التي تسبب أمراض للمستهلك نتيجة لتناول الغذاء الملوث وتم مناقشة المخاطر والأمراض التي تسببها تلك الطفيليات الأولية الممرضة على صحة المستهلك وكيفية منع تلوث منتجات اللحوم بتلك الطفيليات الأولية الممرضة.A total of 45 samples of minced meat, sausage and lunchen (15 of each) and 60 fresh milk samples from caws and sheep were examined for detection of protozoal food borne pathogens. Cryptosporidium parvum and Toxoplasma gondii, could by detected in varying percentages in the examined meat products. The public health significance of the detected protozoal food borne pathogens and the sources of contamination as well as recommendations to protect meat products from contamination with protozoal foodborne pathogens were discussed.